Colocolic intussusception in a child due to a sigmoid polyp - S. Tursini; M. Trinci; R. Palliola; M.L. Perrotta; N. Guarino; M. Galluzzo; V. Briganti (Elsevier, 2020)
Intussusception cases in children are mostly ileocolic, whereas, the colocolic variety is uncommon and few cases have been reported in literature. Together with intestinal malrotation, ileocolic intussusception is frequently the cause of an intestinal obstruction in children and rarely due to a lead point. In children, if present, the lead point is located in the ileum and is related to o lymphoma o lymphangioma or rarely to ectopic mucosa. We describe the case of o 8-year child with colocolic intussusception (CCI) and rectal bleeding due to a voluminous sigmoid polyp. The intussusception was reduced two times in 36h and then the polyp was resected by colonoscopy.